A heteroleptic diradical Cr(iii) complex with extended spin delocalization and large intramolecular magnetic exchange. Issue 36 (2nd April 2020) - Ma, Xiaozhou; Suturina, Elizaveta A.; Rouzières, Mathieu; Wilhelm, Fabrice; Rogalev, Andrei; Clérac, Rodolphe; Dechambenoit, Pierre
Abstract : Ligand-based successive reductions in a heteroleptic Cr(iii ) complex give rise to intended extremely strong metal–radical magnetic interactions. Abstract : Successive chemical reductions of the heteroleptic complex [(tpy)Cr III (tphz)] 3+ (tpy = terpyridine; tphz = tetrapyridophenazine) give rise to the mono- and di-radical redox isomers, [(tpy)Cr III (tphz˙ − )] 2+ and [(tpy˙ − )Cr III (tphz˙ − )] +, respectively. As designed, the optimized overlap of the involved magnetic orbitals leads to extremely strong magnetic interactions between the S = 3/2 metal ion and S = 1/2 radical spins, affording well isolated S T = 1 and S T = 1/2 ground states at room temperature.